National Scarce Skills within the Professional Chef’s Sector in South Africa - Balkaran, Rishidaw; Giampiccoli, Andrea (Journal of Education and Vocational Research, 2013)
Since 1994, South Africa has witnessed an exceptional growth of the tourism sector. The hospitality sector is following a same positive trend however, there is not an appropriate growth of its human resources. South Africa, as many other countries, suffers a skills shortage of catering employees such as executive chefs and cooks. In addition, the historical context of South Africa has produced a specific skewed demographic picture of kitchen staff that now needs to be rebalanced. The skills shortage of kitchen staff could seriously affect the quality of service of the growing hospitality sector. This paper intends to investigate the context and problems related to kitchen staff shortages in South Africa. A literature review of factors such as low wages, unsociable and long hours will be outlined. Thereafter, the specific context of South Africa will be investigated. The specific history of the country has influenced also the hospitality (and kitchen staff) milieu, thus issues in the transformation of the sector will need to be put forward. The paper will conclude with some possible suggestion to decrease the skill shortage in kitchen staff in South Africa.